Implementasi 7 kebiasaan anak Indonesia hebat dalam mewujudkan pembelajaran yang berkarakter - Everyana Frienansia Farahdiba; Feri Tirtoni (IKIP Siliwangi, 2026)
This study aims to describe the implementation of healthy living habits and the character building process of grade IV B students at SDN Sawotratap 2 through a series of habituation activities that are designed in a structured manner and implemented continuously. The focus of the study is directed at the habituation of group work, compliance with school regulations, and the habit of going to bed early which is monitored through a daily habituation journal with the active involvement of parents. The approach used in this study is qualitative with a descriptive design. The research subjects included grade IV B teachers, students, and parents, while data collection techniques were carried out through observation, interviews, and documentation. Data validity was guaranteed through the application of triangulation of sources and methods. The research findings show that the practice of healthy living habits and strengthening students' character have been implemented in a planned, systematic, and consistent manner, both at school and at home. The habituation of group work and compliance with school regulations has been proven to be able to foster attitudes of tolerance, cooperation, responsibility, and social awareness in students. Moreover, the routine of sleeping early, facilitated by parental involvement via daily journals, positively affects students' physical and mental preparedness for engaging in learning activities. These behaviors lead to enhanced focus, emotional balance, and time management discipline. By means of ongoing and repetitive habituation, students come to not only adhere to the rules out of obligation but also assimilate positive values into their everyday way of life. Therefore, the implementation of healthy living habits at SDN Sawotratap 2 plays a crucial role in supporting the development of discipline, responsibility, social awareness, and optimal learning readiness in elementary school students.